Phospholipid biosynthesis is required for stalk elongation in Caulobacter crescentus. - Mansour, J D (1981)
Membrane phospholipid synthesis was inhibited in Caulobacter crescentus by growth of a glycerol auxotroph in the absence of glycerol or by treatment with the antibiotic cerulenin. It was observed that the final step in the swarmer cell-to-stalked cell transition, stalk elongation, was inhibited under these conditions. Since an early effect of inhibiting phospholipid synthesis in C. crescentus is the termination of deoxyribonucleic acid (DNA) replication (I. Contreras, R. Bender, A. Weissborn, K. Amemiya J. D. Mansour, S. Henry, and L. Shapiro, J. Mol. Biol. 138:401-410, 1980), we questioned whether the inhibition of stalk formation was due directly to the inhibition phospholipid synthesis or secondarily to the inhibition of DNA synthesis. Under conditions which inhibited DNA synthesis but permitted phospholipid synthesis, i.e., growth of a temperature-sensitive DNA elongation mutant at the restrictive temperature or treatment with hydroxy-urea, stalk elongation occurred normally. Therefore phospholipid synthesis is required for stalk elongation in C. crescentus.